Horkovodní roštový kotel - Svoboda, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Práce se zabývá návrhem horkovodního roštového kotle, kde výstupem je voda o parametrech 130 °C a tlaku 16 bar. V obsahu celé práce je postupně uveden stechiometrický výpočet, který vychází ze zadaného paliva – dřevní štěpky. Následuje navržení jednotlivých výhřevných ploch podle tepelných výpočtů uvedených v práci. Výpočet je na závěr rozšířen o hydraulické a aerodynamické ztráty. Rozměrový návrh, jako základní schéma, je uvedeno přímo v práci. Podrobnější výkresová dokumentace tvoří přílohu této práce.

This thesis deals with design of hot water grate boiler, where the output is water with parameters 130 °C and pressure 16 bar. In the content of the whole thesis is gradually introduced a stoichiometric calculations, which is based on the specified fuel – wood chips. This is followed by the design of the individual heating surfaces according to the thermal calculations given in the thesis. Finally, the calculation is extended by hydraulic and aerodynamic losses. Dimensional design, as a basic scheme, is shown at thesis. More detailed drawing documentation is attached to this thesis.
Hot Water Grate Boiler
Keywords: Horkovodní kotel; biomasa; dřevní štěpka; tepelný výpočet; hydraulické ztráty; aerodynamické ztráty; ohřívák vody.; Hot water boiler; biomass; wood chips; thermal calculation; hydraulic losses; aerodynamic losses; water heater.